A study on the effect of school and family environments and self-efficacy on health literacy of college students - Wang, Yan; Zhang, Jiayu; Huang, Kai (Frontiers in Public Health, 2024)
Background Health literacy is an important means to improve health outcomes and reduce health disparities. It plays an important role in promoting multiple health-related behaviors of individuals. Numerous studies have demonstrated a number of sociodemographic and school characteristics, and family related factors were related to health literacy among college students. However, these characteristics and factors were relatively unchangeable. Research on the relationship between factors, that can be intervened, and health literacy remains scarce. This study aims to explore the association between personal and changeable environmental factors, and the level of health literacy in college students. Methods A cross-sectional study, which used a stratified random sampling method, was conducted at a university in Wuhan (N = 447). The survey questionnaire included sociodemographic characteristics, the School Environment Questionnaire, the Family Environment Questionnaire, the General Self-Efficacy Scale Questionnaire, and the Health Literacy Questionnaire. We used Spearman correlation tests, and Student’s tests or analyses of variance to describe the relationship among continuous variables. In addition, we employed linear regression analysis to test the mediating effect based on the bias-corrected nonparametric percentile Bootstrap method. Results Factors related to socioeconomic status, such as living costs (p = 0.011), residential area (p = 0.003), annual household income (p = 0.001), and parents’ education level (fathers: p = 0.001; mothers: p = 0.01) and occupation type (fathers: p < 0.001; mothers: p = 0.044), had close correlations with health literacy. School and family environments and self-efficacy had a positive impact on college students’ health literacy (β = 0.235, p < 0.001; β = 0.323, p < 0.001; β = 0.489, p < 0.001). Self-efficacy had a mediating effect on the relationship between school and family environments, as well as health literacy. The total, direct, and indirect effects of the school environment on health literacy were 0.235, 0.157, and 0.078, respectively. The total, direct, and indirect effects of the family environment on health literacy were 0.323, 0.189, and 0.134, respectively. Conclusion This study confirms that improving school and family environments could directly or indirectly increase college students’ health literacy through promoting their self-efficacy. Socioeconomic status has a significant impact on their health literacy. Moreover, other factors that affect students’ health literacy and relationships among self-efficacy, surrounding environments, and health literacy may need to be explored in the future.